Dielectric Conductivity of Cross-Linked Polyurethanes Modified with Heteropolynuclear Cu3Mn Complexes - Gagolkina, Z. O.; Lobko, Eu. V.; Fomenko, A. O.; Kozak, N. V.; Klepko, V. V.; Kokozay, V. M.; Petrusenko, S. R.; Stetsyuk, O. M. (Київський національний університет імені Тараса Шевченка, 2013)
The dielectric and relaxation properties of cross-linked polyurethane, modified with heteropolynuclear Cu3Mn(L4) complexes with various ligands in outer coordination sphere were analyzed by dielectric relaxation spectroscopy. It was shown, that the modifier introduction in polyurethane leads to conductivity level increasing due to: i) complex formation between functional groups of polyurethane and heteropolynuclear compounds and ii) increase in the macrochain mobility.
Keywords: polyurethanes; dielectric conductivity